Detection of zoonotic-borne parasites in Rattus spp. in Klang Valley, Malaysia - Firdaus Mohd-Qawiem; Saulol Hamid Nur-Fazila; Raslan Ain-Fatin; Qian Hui Yong; Md Isa Nur-Mahiza; Abd Rahaman Yasmin (Veterinary World, 2022)
Background and Aim: Rattus spp. are the most common animals capable of adapting to their environment. They can be reservoirs or vectors of diseases that facilitate the transmission of zoonotic-borne parasites to humans. Hence, a study on the detection of parasites in rat populations in urban areas is crucial to prepare for emerging zoonosis. Therefore, this study aims to identify blood parasites, ectoparasites, and helminths in Rattus spp. from wet markets located in Klang Valley, an urban area with a high-density human population. Materials and Methods: A total of 32 rats were trapped in several wet markets in Klang Valley, Malaysia. They were anesthetized for morphometric examination followed by exsanguination. Various parasitological techniques such as perianal tape test, simple flotation, direct examination of the intestine, and fecal smear were performed for intestinal parasite detection; hair plucking, skin scraping, and full body combing for ectoparasite identification; and blood smear, microhematocrit centrifugation, and buffy coat techniques for blood parasite detection. Results: The rats were identified as Rattus rattus (71.9%) and Rattus norvegicus (28.1%). The only blood protozoan found was Trypanosoma lewisi. The ectoparasites identified belonged to two broad groups, mites (Laelaps spp. and Ornithonyssus spp.) and fleas (Xenopsylla cheopis), known to be parasitic zoonotic disease vectors. The zoonotic intestinal parasites were cestodes (Hymenolepis nana), nematodes (Nippostrongylus brasiliensis, Strongyloides spp., Trichuris spp., Capillaria spp., and Syphacia spp.), and intestinal protozoa (coccidian oocysts and Giardia spp.). Microscopic images showing Giardia spp. are the first report of this organism in rats in Malaysia. Conclusion: Rats caught in this urban area of the Klang Valley harbor parasites can pose a potential zoonotic threat to humans, raising public health concerns because of their proximity to densely populated urban areas.